The association between sedentary behavior and obstructive sleep apnea: a cross-sectional study from the NHANES (2007-2008 to 2015-2020) - Song Cai; SiYu Li; YaShi Zhou; JuKun Song; JuXiang Peng (BMC, 2024)
Abstract Background Sedentary behavior (SB) may contribute to obesity and lower extremity fluid retention, which may favor the development of obstructive sleep apnea (OSA). However, linking sedentary behavior to OSA is unclear. The purpose of this study was to determine if there is an association between SB and OSA. Methods Three typical questions in the NHANES questionnaire(①The frequency of feeling excessively sleepy per month. ②The frequency of gasping, snorting or stopping breathing per week. ③The frequency of snoring per week.) have been used for the assessment of OSA. A physical activity questionnaire(On a typical day, the amount of time you spend sitting or reclining.) was used to assess SB. This secondary analysis included National Health and Nutrition Examination Survey (NHANES) participants (unweighted = 20,115). Weighted sample and multiple logistic regression complex sample analysis techniques were used in this study. Results After adjustment for confounders, participants with SB(> 8 h/d) had a higher risk of OSA compared to SB(< 4 h/d). Stratified analysis by gender showed that there was no significant association of SB and OSA in men. However, in women, with SB(< 4 h/d) as the reference, participants with(≥ 4 h/d) had an increased risk of OSA. By age-stratified analysis, the association of SB with OSA was stronger among older participants. Conclusion Analysis in this study showed a positive association between SB and OSA, more pronounced in women and participants older than 60 years old.